IL‐17A promotes susceptibility during experimental visceral leishmaniasis caused by Leishmania donovani. Issue 3 (18th November 2015) - Terrazas, Cesar; Varikuti, Sanjay; Kimble, Jennifer; Moretti, Ellen; Boyaka, Prosper N.; Satoskar, Abhay R.
Abstract : Leishmania donovani is an intracellular parasite that infects professional phagocytes and causes visceral leishmaniasis (VL). The immune response during VL has been extensively studied in the context of T‐helper (Th ) 1 and Th 2 responses. Immunity against this parasite is dependent on IFN‐γ production and subsequent macrophage activation, and the Th 2 response promotes granuloma formation. The cytokine IL‐17A is associated with neutrophilic inflammation. Depletion of neutrophils during experimental VL results in enhanced parasitic loads. Furthermore, although patients resistant to VL showed enhanced levels of IL‐17A in circulation, little is known about the role of IL‐17A during VL infection. Here, we used IL‐17A‐deficient mice and IL‐17A reporter mice to address the role of IL‐17A during VL. IL‐17A –/– mice were highly resistant to VL infection, showing decreased parasites in the liver and spleen. This unexpected phenotype was associated with enhanced IFN‐γ production by T cells and decreased accumulation of neutrophils and monocytes, resulting in reduced number of granulomas. We also found γδ T and Th 17 cells as the main IL‐17A + cells during VL infection. Our data reveal an unexpected role of IL‐17A rendering susceptibility against L. donovani by regulating the IFN‐γ response and promoting detrimental inflammation.—Terrazas, C., Varikuti, S., Kimble, J., Moretti, E., Boyaka, P. N., Satoskar, A. R., IL‐17A promotes susceptibility during experimental visceral leishmaniasis caused by Leishmania donovani . FASEB J. 30, 1135‐1143 (2016). www.fasebj.org